Early positive effects of tree species richness on herbivory in a large‐scale forest biodiversity experiment influence tree growth. (28th March 2015) - Schuldt, Andreas; Bruelheide, Helge; Härdtle, Werner; Assmann, Thorsten; Li, Ying; Ma, Keping; von Oheimb, Goddert; Zhang, Jiayong; Austin, Amy
Summary Despite the importance of herbivory for the structure and functioning of species‐rich forests, little is known about how herbivory is affected by tree species richness, and more specifically by random vs. non‐random species loss. We assessed herbivore damage and its effects on tree growth in the early stage of a large‐scale forest biodiversity experiment in subtropical China that features random and non‐random extinction scenarios of tree mixtures numbering between one and 24 species. In contrast to random species loss, the non‐random extinction scenarios were based on the tree species' local rarity and specific leaf area – traits that may strongly influence the way herbivory is affected by plant species richness. Herbivory increased with tree species richness across all scenarios and was unaffected by the different species compositions in the random and non‐random extinction scenarios. Whereas tree growth rates were positively related to herbivory on plots with smaller trees, growth rates significantly declined with increasing herbivory on plots with larger trees. Our results suggest that the effects of herbivory on growth rates increase from monocultures to the most species‐rich plant communities and that negative effects with increasing tree species richness become more pronounced with time as trees grow larger. Synthesis. Our results indicate that key trophic interactions can be quick to become established in forest plantations (i.e. already 2.5 years after tree planting). Stronger herbivory effects on tree growth with increasing tree species richness suggest a potentially important role of herbivory in regulating ecosystem functions and the structural development of species‐rich forests from the very start of secondary forest succession. The lack of significant differences between the extinction scenarios, however, contrasts with findings from natural forests of higher successional age, where rarity had negative effects on herbivory. This indicates that the effects of non‐random species loss could change with forest succession.